Rodent-borne Leptospira spp. and hantaviruses in Europe - Jeske, Kathrin (Universität Greifswald, Mathematisch-Naturwissenschaftliche Fakultät / Abteilung für Mikrobiologie und Molekularbiologie, 2021)
More than half of the infectious diseases in humans are caused by zoonotic pathogens or pathogens of animal origin that were transmitted to humans a long time ago. Two important rodent-associated zoonotic pathogens are hantaviruses and human-pathogenic Leptospira spp. Both pathogens induce lifelong infection in the rodent hosts that shed the pathogen. Infection with these zoonotic pathogens in humans can cause clinical symptoms. Since some rodents, like the common vole (Microtus arvalis) and the bank vole (Clethrionomys glareolus syn. Myodes glareolus), have cyclic mass reproduction, this can result in years of population outbreaks in an increased number of disease cases in humans. This was found to be the case with the leptospirosis outbreaks in Germany and tularemia outbreaks in Spain, which were traced back to increased common vole density, as well as with the hantavirus disease outbreaks in several European countries, which were associated with bank vole population outbreaks. The aim of this work was to define the distribution and prevalence of different hantaviruses and leptospires as well as their coinfection in different European rodents, with a focus on voles from the genus Microtus and the identification of factors that affect the pathogen prevalence in rodent hosts. Therefore, common voles, bank voles, striped field mice (Apodemus agrarius) and other rodents were screened by molecular methods for the presence and prevalence of Leptospira spp. and different hantaviruses. Additionally, in selected studies, the presence of anti-hantavirus antibodies was screened by enzyme-linked immunosorbent assay (ELISA) using recombinant hantavirus-nucleocapsid proteins. The prevalence of hantavirus, Leptospira spp. and double-infections with both pathogens was analyzed using individual and population-based factors. Small mammals from four different European countries, Spain in the West, Germany and Austria in Central and Lithuania in Northeastern Europe, were included in the studies. With the molecular screenings, two ...